CREDIT CARD POSSESSION AND IMPULSIVE BUYING BEHAVIOR AT MATAHARI DEPARTMENT STORE MANADO TOWN SQUARE (A QUALITATIVE ANALYSIS) - Mangundap, Maria B.; Worang, Frederik G. (Universitas Sam Ratulangi, 2019)
Abstract: Matahari Department Store has been the place for the citizen to buy their clothing attire, either on the daily basis or annually. Matahari Department Store tends to offer discount or promotion to lower the price of the products also being one of the factors that attracts people to come and spend their money there. The people can just make plan to go buy something there or in this case being an impulsive buyer. When people pass by Matahari Department Store they might caught on something like the promotion or discount tags, once they check on the products with the said tags there are chances that they more likely to buy it, thus the impulsive buying take part. The purpose of this study is to find out the customer of Matahari Department Store Mantos that choose credit card as a payment method. Most of the informants gave similar response regarding the advantages to use a credit card because credit card is seen as a convenient and relatively easier way for transaction process, moreover the use of credit card lowers the perceived cost with bigger future use that affects impulsive buying behavior at Matahari Department Store Manado Town Square. This research was conducted in Manado. Qualitative research is deployed and purposive sampling technique is used in the sampling process of the research. This research is mean to be for Matahari Department Store Mantos costumer and there will be 10 representative customers as the sample. Keywords: impulsive buying behavior, credit card.